Obliczenie Pewnej Konstrukcji Przestrzennej - Czulak, J. (Engineering Transactions, 1965)
The present paper proposes a computation method of interaction forces between floor plates. and columns in three-dimensional monolithic structures with a small deformability of floor plates. as compared with that of the columns. The considerations presented concern structures with horizontal floors and vertical columns. The fundamental assumption is that of absolute indeformability of floor plates. To solve the problem the displacement method has been applied. Corresponding formulas and general equations are derived for the fundamental system (Fig. 1). The computation of the construction in the case of the symmetry of system and its loading is: discussed. Besides, the case of hinged joints between plates and columns is also analysed. Finally, the problem of computing compound structures (Figs. 4 and 5) is considered.